Development and Application of the Intelligent Seed Processing Technology and Equipment - Sh. Jia; G. Liu; J. Jia; T. Yang (Сельскохозяйственные машины и технологии)
Seed processing is an important link in the seed industry chain. Crop seed industry is a national strategic and basic core of industry. Drying, cleaning, selecting, grading, coating, packaging and storage of crop seeds are the main measures to realize the precision sowing of crops and the increase of grain yield and income. Continuously improving the intelligence and fi ne level of seed processing equipment is of great signifi cance to ensure the production and supply of excellent seeds and the stability of agricultural production. This paper describes the development status of modern seed processing equipment technology in China, introduces the establishment of seed processing equipment engineering technology research center, taking maize, rice, wheat and cotton seed processing technology and machinery as an example, describes the key technologies and technological process of the breakthrough in the major crop seed processing, analyzes the existing problems of seed processing equipment in China at this stage as well as the development trend in the future, provides a reference for government decision makers in resolving the problem of mechanical damage in the process of seed processing and further improving the intellectualization level of seed processing, promotes the common progress of the global seed processing equipment technology.